p-Phosphonated Calix[n]arene Stabilizes Superparamagnetic Nanoparticles for Nitrate and Phosphate Uptake - D'Alonzo, N.; Eggers, P.; Eroglu, Ela; Raston, C. (Wiley - V C H Verlag GmbH & Co. KGaA, 2017)
© 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.Highly faceted superparamagnetic magnetite nanoparticles roughly 11nm in diameter are readily accessible in the presence of p-phosphonated calix[n]arenes of different ring sizes (n=4, 5 and 6), through the use of a simple co-precipitation technique. In contrast, the larger calix[8]arene affords spherical particles of comparable size. The maximum magnetization is 70-60emug-1, which decreases with increasing size of the calixarene macrocycle, and the evidence indicates that the calixarenes bind to the surface of the nanoparticles via the phosphonate head groups rather than the phenolic oxygen centers. The stabilized nanoparticles show dual functionality: they remove up to 62% of nitrate nitrogen and 48% of phosphate from an aqueous effluent after 24hours at concentrations of only 1gL-1 of calixarene-coated nanoparticles.